(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The article presents the results of three-year research on the complex impact of various combinations of sowing timeframes and pre-sowing treatments of seeds with agents containing different active substances on the leaf surface formation over time and symbiotic activity of soybean plants of different ripeness groups. Problem Articulation. Unfortunately, high genetic productivity potentials of modern soybean cultivars are far from fully exposed. This results from, among other causes, insufficient involvement of technological measures of plant growth and development improvement, in particular, pre-sowing treatment of seeds, and application of growing technology elements without taking into account unique features of cultivars. Based on this, the purpose of our study was to find ways to enhance the fulfilment of the genetic potentials of Ukrainian soybean cultivars differing in morphobiological characteristics via optimizing sowing time and choosing the best variants of pre-sowing treatments of seeds, which will ensure increased resistance of plants to complex unfavorable factors and create better conditions for plant growth and development. Methods. The study was carried out in the eight-field, grain-fallow-intertilled crop rotation of the Crop Production Department, which is part of the experimental field of the V.V. Dokuchaev KhNAU. The multi-factorial experiment was designed in split plots in four replications by conventional technique. The first-order plots (factor A) were three soybean cultivars: ‘Annushka’, ‘Kobza’, and ‘Malvina’; the second-order plots (factor B) were three sowing timeframes: early (6–8 ºС), medium (10–12 ºС), and late (14–16 ºС); and the third-order plots (factor C) were five variants for pre-sowing treatment of seeds with agents containing different active substances: 1 – no treatment (control); 2 – Humisol (biological), 3 and 4 – Adaptophyt and Growth Concentrate, respectively (growth morpho-regulators); 5 – Fundazol (fungicide). Results. All soybean cultivars selected for this study had the largest leaf surfaces at the grain filling onset. On average across the years and seed treatments, it was 39,900, 37,400, and 35,000 m2/ha in soybean cultivars (Cvs.) ‘Malvina’, ‘Kobza’, and ‘Annushka’, respectively. At all record timepoints, the studied cultivars had the largest leaf surfaces when sown within the medium timeframe (10–12ºС). In particular, the leaf surface in cultivar (Cv.) ‘Malvina’ at the grain filling onset averaged (across the years and pre-sowing treatments of seeds) 37,700, 43,100, and 39,000 m2/ha when sown early (6–8ºС), mediumly (10–12ºС), and late (14–16ºС), respectively. In Cv. ‘Kobza’, it was 35,600, 40,100, and 36,400 m2/ha, respectively; and in Cv. ‘Annushka’, it was 33,200, 36,700, and 35,000 m2/ha, respectively. On the whole in the experiment, the largest leaf surface at the anthesis onset, grain filling onset, and grain ripening onset was recorded for Cv. ‘Malvina’ sown within the medium timeframe (10–12ºC) after pre-sowing treatment of seeds with the growth regulator Adaptophyt: 26,200, 46,400, and 40,200 m2/ha, respectively. The highest total nodule weight of 0.685 mg/plant on average across three years was observed on roots of Cv. ‘Kobza’ sown within the medium timeframe after pre-sowing treatment of seeds with Humisol. The highest active nodule weight of 0.649 mg/plant was also noted in this experimental variant. Both the total nodule weight and active nodule weight underwent the greatest changes under the influence of pre-sowing treatment of seeds. Of the studied agents, the biological Humisol was the best choice in this regard. In particular, on average across the years, cultivars and sowing timeframes, the weight of active nodules on roots was 0.137 mg/plant in this variant or almost 37.0% higher than in the untreated variant (control). Quite predictably, of the studied agents, the fungicide Fundazol showed the worst result. Both the number and weight of nodules in this variant were significantly lower than after pre-sowing treatments of seeds with Humisol or morpho-regulators; however, they were higher than in the untreated variant. Conclusions. The soybean cultivars selected for this study had the largest leaf surfaces at the anthesis, grain filling, and grain ripening onsets when sown within the medium timeframe (10-12 ºС) after pre-sowing treatment of seeds with the growth regulator Adaptophyt or the biological Humisol. The symbiotic activity of plants of the investigated soybean cultivars was also highest in these variants. Based on the above-presented data, these combinations can be recommended for production, since larger leaf surfaces and higher symbiotic activity ensure greater yields of grain.